Diseño de un prototipo de Electrolinera para la recarga de vehículos eléctricos usando Energía Fotovoltaica. - Casa Cárdenas, Álvaro Dennis (2023)
The objective of this technological work is to develop a charging system for electric vehicles, through the application of a photovoltaic system with this type of system, it seeks to reduce the levels of pollution that are currently produced by conventional mobility systems. , existing in the area. As a consideration, costs related to equipment are taken into account, being able to size for electric vehicles of the Scooter type with powers of up to 300W, based on this type of vehicle, the design of the vehicle charging system called electric station is carried out, characterizing the study area. where the system will be implemented for its operation.